PROTOTYPE ALAT PENGONTROL PH AIR DAN SUHU UNTUK AQUARIUM IKAN PBASS BERBASIS INTERNET OF THINGS - Sadi, Sumardi; Susanto, Andri; Apriansyah, Sandy Adam (Jurnal Teknik Elektro, 2025)
PBASS fish is one of the ornamental fish species that is in great demand in Indonesia. Good water quality is very important for the health and survival of fish in an aquarium. One crucial parameter is the pH of the water, which must be maintained within the optimal range according to the type of fish being kept. This study aims to develop a prototype of an Internet of Things (IoT)-based water pH controller for PBASS fish aquariums. This system is designed using NodeMCU ESP8266 as a microcontroller, a pH sensor to measure the acidity level of the water, and the Blynk application to monitor and control the water pH in real-time. System testing shows that this tool is able to measure and stabilize the water pH according to the needs of PBASS fish, as well as provide notifications to users via the application if there is a significant change in pH. The results of this study are expected to help freshwater ornamental fish hobbyists in maintaining ideal environmental conditions for their pet fish, thereby reducing the risk of stress and disease due to uncontrolled pH fluctuations.